DEVELOPMENTAL CHANGES IN THE GENITAL ORGANS OF YOUNG MALE MICE ASSOCIATED WITH LICORICE EXTRACT CONSUMPTION BY MOTHERS BEFORE AND DURING GESTATION. (Iraqi Journal of Medical Sciences, 2016)
Background: Licorice (Glycyrrhiza glabra) is one of the most popular plants and widely consumed as a medicinal herb, which is used mainly in treatment of inflammations and improvement of reproductive performance in both females and males.Objective: To detect the effect of licorice extract consumed by pregnant females on gonadal development of their male offspring.Materials & Methods: Mature female mice(No:60), were divided into: experimental group(G,30mice), which subdivided into 3 equal subgroups: G1,G2 and G3(10 mice for each), given extract of licorice root(1gm/kg body weight),immersed in distilled water for 3 weeks before mating (G1) or for 6weeks before and during pregnancy (G2) or for 3 weeks during pregnancy time only(G3) . The other main group (C) was considered as control group subdivided as that with the experimental group but they were given distilled water only. Number and weights of male's newborn were recorded. After 40 days, weights of their bodies and testes were recorded; histological sections were prepared for the testes to detect the presence of mature sperms and to measure the diameters of semineferous tubules and thickness of their germinal walls.Results: Highly significant increase (P
Keywords: fetal development; male gonads; pregnancy; licorice; mice